(untitled) (Journal of history-rus, 2023)
Kazakhstan in the era of globalization has established itself as a multi-ethnic, multi-cultural country. Due to many historical and political factors, when Kazakhstan declared national independence in 1991, its population consisted of 130 different ethnic nationalities and 42 different religious denominations. Despite the possibility of ethnic and religious conflicts, tolerance and mutual understanding prevail in Kazakhstan. This attitude, supported by the government and the openness of the Kazakhstani people, has led them to find a balance between their different backgrounds and religious beliefs in all aspects of daily life, starting with leisure to activities in their professional environment. The purpose of the article is to analyze the contribution of exiled Polish figures to the social atmosphere and cultural transformation of Kazakhstan, tells about individual representatives of the Polish ethnic group who contributed to the socio-economic development of East Kazakhstan. The authors come to the conclusion that an objective study of the problem of the history of Poles on the territory of Kazakhstan is of great scientific importance both for ethnogeographic history and for the consolidation of Kazakh society and the consolidation of national integrity in modern conditions. The methodological basis of the research is the general scientific methods of historical research and scientific analysis. At the same time, system-structural analysis is of great importance, which allows us to consider any developing phenomenon as a certain system with an appropriate structure and functional significance. The interdisciplinary nature of the problem determines the use of a complex of various research methods based on a systematic approach to international relations, comparative analysis and other methods that provide results that objectively reflect the current state of the problem under study. Along with these most important provisions, the criteria of historical analysis are included in the methodological basis, the objectivity of historical truth and the degree of its compliance with actual historical knowledge are of great importance. Special attention was paid to source analysis, critical analysis of sources and their comparative study to obtain the most objective data. The article is based on the principles of systematic, comparative-historical, ethnopolitical and institutional analysis, including such general scientific methods as deduction, induction, analysis, synthesis, forecast.